2022
DOI: 10.1128/spectrum.00651-22
|View full text |Cite
|
Sign up to set email alerts
|

ATP Bioluminescence Assay To Evaluate Antibiotic Combinations against Extensively Drug-Resistant (XDR) Pseudomonas aeruginosa

Abstract: Combining antibiotics is one of the few strategies available to overcome infections caused by multidrug-resistant bacteria. Time-kill curves are usually performed to evaluate antibiotic combinations, but obtaining results is too laborious to be routinely performed in a clinical laboratory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Non-destructive food quality determination is of great importance in food technology research, among which ultra-weak bioluminescence (UWLE) has been used as a detection tool for the identification of abiotic [ 10 ] and biotic [ 11 ] stressors in plants, as well as for food quality and safety assessment [ [12] , [13] , [14] , [15] , [16] , [17] , [18] ]. In their review work, Nematollahi et al [ 12 ] found UWLE measurements to be effectively used for the determination of tomato maturity stages, quality of sweet potato, and also there was correlation found UWLE signal intensity and the viability and germination rate of rice and coffe seeds.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Non-destructive food quality determination is of great importance in food technology research, among which ultra-weak bioluminescence (UWLE) has been used as a detection tool for the identification of abiotic [ 10 ] and biotic [ 11 ] stressors in plants, as well as for food quality and safety assessment [ [12] , [13] , [14] , [15] , [16] , [17] , [18] ]. In their review work, Nematollahi et al [ 12 ] found UWLE measurements to be effectively used for the determination of tomato maturity stages, quality of sweet potato, and also there was correlation found UWLE signal intensity and the viability and germination rate of rice and coffe seeds.…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon, which can be monitored by a sensitive charge coupled device (CCD) camera and visualized via proper software supplementation [ 14 ], provides information about the organism's oxidative state, which is, in the case of fruits, related to the maturity state and/or quality traits [ 12 , 15 ]. Altemimi et al [ 16 ] investigated food contact surface microbial contamination, tested the efficiency of sanitizers via ATP-bioluminescence method and successfully detected Escherichia coli and Staphylococcus aureus on surfaces and tools also Pseudomonas aeruginosa [ 17 ]. Also, ATP-bioluminescence sensor and plate counting techniques produced comparable results thus make this techniquie possible for on-site measurement as well [ 18 ].…”
Section: Introductionmentioning
confidence: 99%